Pelatihan dan Pendampingan Pembelajaran Ilmu Fiqih di Desa Tanggalrejo Jombang - Mohamad Nasirudin; Mochammad Syafiuddin Shobirin; M Aliyul Wafa; Ahmad Hamdan Zainul Hasan; Muhammad Ichlasul Amal; Widya Pertiwi; Laila Ma'rufah (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2024)
Daterejo Village is a village in Mojoagung District, Jombang Regency, East Java Province. has hamlets namely, Kalibening, Mojoranu, Semen, Jonggrong, Sonokerep and Daterejo. The Daterejo State Elementary School Education Service is one of the educational institutions that was founded in 1963. In Kalibening Hamlet there is a BABUSSALAM Islamic Boarding School and MI, MTs, MA, STAI schools. The Diniyyah Miftahussalam Madrasah students in Daterejo Village have many religious fields but are still lacking in depth. His religious studies, especially in the field of Fiqh. Therefore, we had the idea to hold Fiqh Learning Training and Mentoring for Santri Madrasah Diniyyah Miftahussalam in Daterejo Village, Mojoagung District. By using the practical Fiqh book learning module chapter thaharah (purification) and prayer. Method The approach taken for community service in Daterejo village is by using the SL (Service Learning) method. One of them is by applying coercion methods, educational games, training and local community approaches so that indirectly, students in Daterejo village can grasp the material well. Based on the results of community service activities on the PPM theme, the following can be concluded: (a) Santri Madrasah Diniyah TPQ Miftahussalam have become more understanding and can also carry out Fiqh practice regarding the chapter on purification and prayer properly and correctly. (b) Fiqh learning at TPQ Madrasah Diniyah Miftahussalam now has a guidebook regarding how to practice Fiqh related to the chapter on purification and prayer. (c) Teachers and Students of Madrasah Diniyah TPQ Miftahussalam Become increasingly motivated in getting to know the chapter on purification and prayer.